The Acceptance Of Digital Banking Among Old Adults: An Application Of Technology Acceptance Model - Amos Daniel, Lejau (Universiti Malaysia Sarawak (UNIMAS), 2022)
Recently, there has been a lot of focus on the development and application of technology. In Malaysia, the transition to a digital banking infrastructure-based financial system may propel the country toward a high-income economy. The technology helps the banking transaction become much more convenient. However, the existence of technology does not appear to be appreciated. This could be due to some people who are not ready to embrace the latest technology in financial industry. Therefore, the purpose of this study is to investigate the variables that affect Malaysian users' intention especially the old adults in using the digital banking services such as mobile banking. This study will also propose the technology acceptance model (TAM) as a tool to analyse the elements that significantly affect Malaysian users' intentions to utilise digital banking services. The two most important variable, perceived usefulness and perceived ease of use have strong impact on user’s intention in using the digital banking system. Their intention will determine whether they will adopt the digital banking